Contribution of biosignals for emotional analysis on image perception - Alexandre, I; Felizardo, V; Pombo, N; Garcia, N (TechAAL 2016 : 2nd IET International Conference on Technologies for Active and Assisted Living : IET London: Savoy Place, 24-25 October 2016, 2016)
An emotion is the result of a defensive behavior, in relation to a particular stimulus that a human being is subject to. This behavior is marked by physiological changes such as increased heart rate and activation of the sweat glands. This study aimed to verify how the viewing of images cause changes in the physiological behavior of a person. For that multiple images with a certain emotional impact were selected, such as: negative images, positive images and neutral images. This paper describes this set of experiments, where selected images from a validated image bank were shown to healthy young subjects, while their electrocardio and electrodermal activity signals were recorded. This paper also describes the obtained results and suggests new research in this area. The collected biosignals are publicly available for further research at the laboratory media wiki.